Allocating active power loss with network reconfiguration in electrical power distribution systems - Ambika Prasad Hota; Sivkumar Mishra; Debani Prasad Mishra; Surender Reddy Salkuti (Institute of Advanced Engineering and Science, 2021)
This paper presents a branch exchange (BE) based heuristic network reconfiguration technique where, the proposed bus classification strategy remodels dynamically as per the modified topology in order to provide a reconfigured network with minimum loss. Further, for fair allocation of the active power losses, it develops a new active power loss allocation (APLA) technique which eradicates the influence of cross-term analytically from loss formulation without any assumptions and approximations. The effectiveness of the proposed procedure has been investigated against other established methods using a 69-bus radial distribution network (RDN). The results of APLA achieved for original and reconfigured 69-bus RDN are found to be promising and judicious as regard to their load demands and geographical locations. The implementation of present reconfiguration procedure provides a total loss reduction benefit of 55.73% to the utility which highlights the significance of the developed procedure against other established techniques.